The burden of anxiety among people living with HIV during the COVID-19 pandemic in Pune, India - Marbaniang, Ivan (Res Sq, 2020)
INTRODUCTION: Globally, India has the third largest population of people living with HIV (PLHIV) and the second highest number of COVID-19 cases. Anxiety is associated with antiretroviral therapy (ART) nonadherence. It is crucial to understand the burden of anxiety and its sources among Asian Indian PLHIV during the COVID pandemic, but data are limited. METHODS: During the first month of government mandated lockdown, we administered an anxiety assessment via telephone among PLHIV registered for care at a publicly funded antiretroviral therapy (ART) center in Pune, India. Generalized anxiety was defined as GAD-7 score ≥10. Sociodemographic and clinical variables were compared by anxiety status (GAD-7 score≥10 vs GAD-7 score<10). Qualitative responses to an open-ended question about causes of concern were evaluated using thematic analysis. RESULTS: Among 167 PLHIV, median age was 44 years (IQR 40–50); the majority were cisgender women (60%) and had a monthly family income <200 USD (81%). Prior history of tuberculosis and other comorbidities were observed in 38% and 27%, respectively. Overall, prevalence of generalized anxiety was 25% (n=41). PLHIV with GAD-7 score ≥10 had fewer remaining doses of ART than those with lower GAD-7 scores (p=0.05). Thematic analysis indicated that concerns were both health related and unrelated, and stated temporally. Present concerns were often also projected as future concerns. CONCLUSIONS: The burden of anxiety was high during COVID lockdown in our population of socioeconomically disadvantaged PLHIV in Pune and appeared to be influenced by concerns about ART availability. The burden of anxiety among PLHIV will likely increase with the worsening pandemic in India, as sources of anxiety are expected to persist. We recommend the regular use of short screening tools for anxiety to monitor and triage patients as an extension of current HIV services.